2019
DOI: 10.3319/tao.2018.11.15.02
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the 6 February 2018, Hualien earthquake sequence through catalog compilation

Abstract: In this study, we compiled the Central Weather Bureau (CWB) data in order to study the Gutenberg-Richter magnitude-frequency slopes (i.e., b-values) and seismicity rates of significant earthquake sequences in the area of Hualien. A total of ten events between 1973 and 2018 were selected for analysis. Using time windows 72 h before and after the main shock, we first examined the existence of detectable foreshocks and then applied the Gutenberg-Richter law and Omori's law to determine the b-value and seismicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…It not only shows the improvements on short-term hazard evaluation but also independently supports the multi-sequence nature of the 2018 Hualien earthquake. This study also confirmed the low bvalue obtained in 72 hr after Hualien main shock in Chen et al (2019c). Chen et al (2019b) demonstrates the efficiency of the CWB Early Warning System on the 2018 Hualien earthquake sequence.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…It not only shows the improvements on short-term hazard evaluation but also independently supports the multi-sequence nature of the 2018 Hualien earthquake. This study also confirmed the low bvalue obtained in 72 hr after Hualien main shock in Chen et al (2019c). Chen et al (2019b) demonstrates the efficiency of the CWB Early Warning System on the 2018 Hualien earthquake sequence.…”
supporting
confidence: 83%
“…Two studies concern the seismicity rate of the Hualien sequences that are related to the hazard potential. Chen et al (2019c) explored the temporal evolution of the 2018 Hualien earthquake sequence and other major events previous occurred in the nearby region based on the CWB seismicity catalogues. For both foreshocks and aftershocks of the 2018 Haulien sequence, the seismicity rates (K-values) are relatively high among all 11 studied events, while the b-values are almost the lowest (0.63 and 0.68), which is also significantly below the long term background average (0.99).…”
mentioning
confidence: 99%
“…The M L 6.2 earthquake with epicentre (24.10°N, 121.73°E) and hypocentre at depth 10.6 km occurred at 2350 LT, 6 February 2018 near Hualien, Taiwan (Chen et al 2019). To have a reliable analysis of the aftershock hazard after the Hualien shock, we employ the earthquake catalogue published by the Central Weather Bureau (CWB) at http://gdms.cwb.gov.tw/index.php.…”
Section: Resultsmentioning
confidence: 99%
“…Thousands of aftershocks were recorded by Geophysical Database Management System (https://gdms.cwb.gov.tw/ index.php) of CWB within 14 days . Aftershocks were propagated southward from the hypocenter of the mainshock to the Longitudinal Valley Chen et al 2019).…”
Section: Introductionmentioning
confidence: 99%